Evaluation of the equality of medial rectus advancement to medial rectus resection for consecutive exotropia - Emrah Öztürk; Abuzer Gündüz; Ercan Ozsoy (Cukurova Medical Journal, 2022)
Purpose: The aim of this study was to analyze the amount of medial rectus (MR) advancement in the treatment of consecutive exotropia by comparing it with the amount of MR resection in a sample of patients with constant exotropia and evaluate the effectiveness of MR advancement with lateral rectus (LR) recession in the management of consecutive exotropia. Materials and Methods: A retrospective chart review of patients who underwent unilateral MR strengthening with LR weakening due to consecutive or constant exotropia was performed. Patients with consecutive exotropia underwent MR advancement with LR recession, and those with constant exotropia underwent MR resection with LR recession. The surgical dosages were determined according to a standard table. A successful result was defined as alignment within 10 prism diopters of orthotropia. Results: A total of 36 patients fulfilled the inclusion criteria: 18 had consecutive exotropia and 18 had constant exotropia. Successful alignment was obtained in 83.3% of patients with consecutive exotropia and 88.9% of patients with constant exotropia. There was no difference between the amount of MR advancement performed in consecutive patients with exotropia and the amount of MR resection performed in patients with constant exotropia. Postoperatively, while consecutive exotropes with a poor result showed overcorrection, constant exotropes with a poor result showed undercorrection. Conclusion: This study suggests that there is no difference between the amount of previously recessed MR advancement and that of untouched MR resection. They also showed that MR advancement with LR recession is an effective means of correcting secondary exotropia.